Photodissociation of aromatic molecules by coincidence spectroscopy - Pihlava, Lassi (fi=Turun yliopisto|en=University of Turku|, 2025)
This thesis presents five studies on the gas-phase photodissociation dynamics of eight aromatic molecules: nimorazole, metronidazole, tetrabromothiophene, diiodothio phene, 2-nitroimidazole, 4-bromo-2-nitroimidazole, 4-bromo-5-nitroimidazole, and 2-bromo-5-iodo-4-nitroimidazole. The work is fundamental research on molecular physics, investigating how the molecules break down following photoionisation. All the samples were powders at room temperature and atmospheric pressure. The dissociation mechanisms could be studied at the molecular level on isolated molecules by evaporating the samples in a vacuum. Molecules in the gas phase were ionised using UV radiation and X-rays. The ensuing fragmentation processes were then investigated using ion time-of-flight spectroscopy, electron spectroscopy, and coincidence methods. Two of the articles concern the photodissociation dynamics of thiophenes. Em phasis has been put on analysing certain major fragmentation pathways in detail. The remaining articles focus on nitroimidazoles and aspects of their dissociation dynamics that may explain the radiosensitization properties possessed by some nitroimidazoles. The introductory section of the thesis summarises the publications and covers the theoretical background, experimental details, and research context. Among the key results are i) an explanation for the difference in radiosensitization efficacy between nimorazole and metronidazole, ii) a dissociation model of dicationic tetrabromothiophene, iii) time-scale information on dissociation of dica tionic diiodothiophene, iv) a conclusion that heavy-element-substituted nitroimida zoles seem potential candidates for bifunctional radiosensitizer drugs from a molec ular physics point of view.